Endoscopic and histopathologic features of Anti‐PD‐1‐related collagenous colitis. Issue 1 (11th January 2022) - Kikuchi, Hidezumi; Sakuraba, Hirotake; Akemoto, Yui; Hosoi, Kazuhiro; Murai, Yasuhisa; Hoshi, Kentaro; Fukutoku, Yukari; Asari, Taka; Sawada, Yohei; Hasui, Keisuke; Tatsuta, Tetsuya; Hiraga, Hiroto; et al.
Abstract: Objectives: Cancer patients treated with immune checkpoint inhibitors occasionally show persistent diarrhea accompanied by endoscopic features of ulcerative colitis. The endoscopic mucosal inflammation may appear mild in some patients compared to the clinical severity, which can make choosing a treatment challenging. In this study, we evaluated the factors that support the continuation of chemotherapy by assessing the endoscopic and histopathological characteristics of patients who experienced diarrhea after immune checkpoint inhibitor administration. Methods: This study included eight patients who were diagnosed with collagenous colitis based on pathological assessments. We retrospectively investigated these patients' backgrounds, laboratory data, and computed tomography images that were extracted from their medical records. We also summarized their endoscopic and pathologic findings. Results: All eight patients were being treated with anti‐programmed cell death‐1/programmed cell death‐ligand 1 therapeutic agents and had a recent history of oral proton pump inhibitor therapy. The anti‐programmed cell death‐1‐related collagenous colitis in these cases was characterized by endoscopically mild mucosal inflammation, high fecal calprotectin levels, and a lower frequency of intestinal wall thickening on computed tomography. Histological assessments showed CD8 + lymphocytes predominantly infiltrating the lamina propria and crypts of the colonic mucosa. Suspending the proton pump inhibitor therapy relieved the patients' symptoms and allowed the continuation of the anti‐programmed cell death‐1/programmed cell death‐ligand 1 therapy. Conclusions: Anti‐programmed cell death‐1‐related collagenous colitis is reversible; appropriate diagnosis of adverse events is crucial for the continuation of immune checkpoint inhibitor therapy.